Belimumab: a technological advance for systemic lupus erythematosus patients? Report of a systematic review and meta-analysis. Issue 7 (18th July 2013) - Kandala, Ngianga-Bakwin; Connock, Martin; Grove, Amy; Sutcliffe, Paul; Mohiuddin, Syed; Hartley, Louise; Court, Rachel; Cummins, Ewen; Gordon, Caroline; Clarke, Aileen
Abstract : Objectives: To undertake a systematic review and meta-analysis to investigate clinical effectiveness of belimumab for patients with systemic lupus erythematosus (SLE) and antinuclear and/or anti-double-stranded DNA (dsDNA) autoantibodies. Methods: We searched eight electronic databases and reference lists for randomised controlled trials (RCTs) of belimumab against placebo or best supportive care. Quality assessment and random effects meta-analysis were undertaken. Design: A meta-analysis of RCTs. Participants: 2133 SLE patients. Primary and secondary outcome measures: SLE Responder Index (SRI) at week 52. Results: Three double-blind placebo-controlled RCTs (L02, BLISS-52 BLISS-76) investigated 2133 SLE patients. BLISS-52 and BLISS-76 trials recruited patients with antinuclear and/or anti-dsDNA autoantibodies and demonstrated belimumab effectiveness for the SRI at week 52. Ethnicity and geographical location of participants varied considerably between BLISS trials. Although tests for statistical heterogeneity were negative, BLISS-52 results were systematically more favourable for all measured outcomes. Meta-analysis of pooled 52-week SRI BLISS results showed benefit for belimumab (OR 1.63, 95% CI 1.27 to 2.09). By week 76, the primary SRI outcome in BLISS-76 was not statistically significant (OR 1.31, 95% CI 0.919 to 1.855).